The production impact of cash-for-clunkers: Implications for stabilization policy - Adam Copeland; James Kahn (Federal Reserve Bank of New York, 2011)
Stabilization policies frequently aim to boost spending as a means to increase GDP. Spending does not necessarily translate into production, however, especially when inventories are involved. We look at the cash-for-clunkers program that helped finance the purchase of nearly 700,000 vehicles in 2009. An analysis of auto sales and production movements reveals that the program did prompt a large spike in sales. But the program had only a modest and fleeting impact on production, as inventories buffered the movements in sales. These findings suggest caution in judging the efficacy of such policies by their impact on spending alone.
Keywords: E23; E65; L62; 330; cash-for-clunkers; automobiles; stimulus